In situ microradioscopy and microtomography of fatigue‐loaded dental two‐piece implants. (8th October 2015) - Wiest, Wolfram; Zabler, Simon; Rack, Alexander; Fella, Christian; Balles, Andreas; Nelson, Katja; Schmelzeisen, Rainer; Hanke, Randolf
Abstract : Synchrotron real‐time radioscopy and in situ microtomography are the only techniques providing direct visible information on a micrometre scale of local deformation in the implant–abutment connection (IAC) during and after cyclic loading. The microgap formation at the IAC has been subject to a number of studies as it has been proposed to be associated with long‐term implant success. The next step in this scientific development is to focus on the in situ fatigue procedure of two‐component dental implants. Therefore, an apparatus has been developed which is optimized for the in situ fatigue analysis of dental implants. This report demonstrates both the capability of in situ radioscopy and microtomography at the ID19 beamline for the study of cyclic deformation in dental implants. The first results show that it is possible to visualize fatigue loading of dental implants in real‐time radioscopy in addition to the in situ fatigue tomography. For the latter, in situ microtomography is applied during the cyclic loading cycles in order to visualize the opening of the IAC microgap. These results concur with previous ex situ studies on similar systems. The setup allows for easily increasing the bending force, to simulate different chewing situations, and is, therefore, a versatile tool for examining the fatigue processes of dental implants and possibly other specimens.